Motivation and Sense of Belonging in the Large Enrollment Introductory General and Organic Chemistry Remote Courses - Charles T. Cox; Nicole Stepovich; Alexandra Bennion; Jessie Fauconier; Nicole Izquierdo (MDPI AG, 2021)
The rapid shift from face-to-face to remote instruction in 2020 has resulted in recalibration of lecture and laboratory pedagogy. This research analyzed the impact of remote learning on student motivation and sense of belonging in large enrollment chemistry courses. Student responses were parsed according to specific demographics including gender, academic standing, first-generation status, and ethnicity. Research objectives included the analysis of how remote learning impacted specific demographics to develop guidelines for best practices moving forward for hybrid or online courses. Our findings show that second year students (sophomores) were the most impacted of the academic standing cohorts. Sophomores reported a statistically greater change in motivation after the start of the semester and statistically lower satisfaction with their performance on assignments. Females reported statistically lower motivation and a statistically lower sense of belonging in the course and science, technology, engineering, and mathematics (STEM) fields. Black/African students reported a statistically lower motivation for remote learning than Asian/Pacific Islander and White/Caucasian students. Finally, both White/Caucasian and Black/African students reported a statistically lower sense of belonging in the course and in STEM fields than Asian/Pacific islander students. Finally, statistical differences were not observed based upon first-generation status. The research indicates that students were differentially impacted by the shift to remote learning. From these findings, a stronger understanding of how specific demographics are differentially impacted by remote learning in STEM courses is provided, granting greater insight into best practices moving forward.